Risk Choice and Voluntary Disclosure - An, Byeong-Je; Pae, Suil (The Accounting Review, 2026)
ABSTRACT This paper presents a model in which investors price risk and a firm makes an investment to reduce its cash flow risk. Subsequently, the firm may or may not privately receive information about the future cash flow, whose disclosure is under its discretion. We show that the equilibrium cash flow precision increases with investor risk aversion, but decreases with the likelihood that the firm has private information and the quality of that information. In addition, the equilibrium probability of disclosure increases when the firm is more likely to have higher-quality private information, but it may increase or decrease when investor risk aversion increases. Using these comparative statics, we rationalize mixed empirical findings on the relation between risk and disclosure as equilibrium outcomes. The model is extended to a setting where the firm also makes an investment to increase the mean of its future cash flow. JEL Classifications: D61; G14; M41.